Detection of Helicobacter pylori in Swab Samples from Gastritis Patients Using Polymerase Chain Reaction (PCR) - Dewinta Nur Alvionita; Srianingsih Lestari Ma’bi; Nurlaela Alydrus (Jurnal Biologi Tropis, 2026)
Gastritis is a choronic inflammation of the gastric mucosa that can lead to atrophy and is often caused by Helicobacter pylori infection through urease activity that triggers gastric inflammation and related diseases.. This study aimed to detect Helicobacter pylori in swab samples from patients with gastritis using the Polymerase Chain Reaction (PCR) method. A descriptive qualitative study with a cross-sectional design was conducted at Stella Maris Hospital, Makassar. Fifteen swab samples from gastritis patients were analyzed using PCR targeting a 294 bp DNA fragment. All samples showed negative results, indicated by the absence of DNA bands at the target size. Helicobacter pylori was not detected in swab samples from gastritis patients. The negative findings may be attributed to limitations of swab sampling outside the stomach, the absence of bacterial transfer during reflux, or gastritis caused by factors other than H. pylori.